2000
DOI: 10.7224/1537-2073-2.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Medicine and Multiple Sclerosis: An Objective Review from an American Perspective

Abstract: The use of complementary and alternative medicine (CAM), or unconventional medicine, may be challenging for health care providers in the United States. There are several definitions of CAM, and therapies that are considered alternative in one country may be conventional in other countries. Unconventional medical practices may be used instead of, or in addition to, conventional medical therapy. It may be difficult for people with multiple sclerosis (MS) to obtain reliable MS-relevant CAM information, and there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The reported functions of phytochemicals of DM leaf on inflammation and cell protection as well as our current finding of DM leaf function in myelination indicate that DM leaf extract can be considered as a candidate for relieving the symptoms of progressive multiple sclerosis, even as a complex. Medicinal plants used in multiple sclerosis care report their benefits in relieving spasticity, pain, tremor and depression [67] and enhancing fatty acid metabolism and lymphocyte function [68,69]. However, to our knowledge, no study has explored the function of medicinal plants on OL differentiation/myelination, which is a critical step for remyelination in multiple sclerosis, and our result that DM leaf extracts affect OL development is the first observation as far as we know.…”
Section: Discussionmentioning
confidence: 74%
“…The reported functions of phytochemicals of DM leaf on inflammation and cell protection as well as our current finding of DM leaf function in myelination indicate that DM leaf extract can be considered as a candidate for relieving the symptoms of progressive multiple sclerosis, even as a complex. Medicinal plants used in multiple sclerosis care report their benefits in relieving spasticity, pain, tremor and depression [67] and enhancing fatty acid metabolism and lymphocyte function [68,69]. However, to our knowledge, no study has explored the function of medicinal plants on OL differentiation/myelination, which is a critical step for remyelination in multiple sclerosis, and our result that DM leaf extracts affect OL development is the first observation as far as we know.…”
Section: Discussionmentioning
confidence: 74%
“…It is important for conventional healthcare providers to recognize that, because treatment options may be limited, people with MS may be willing to make treatment decisions with limited information [4]. Also, it is important to acknowledge that, like some unconventional therapies, some conventional MS therapies and practices have limitations and may not be entirely evidence-based.…”
Section: Opinion Statementmentioning
confidence: 98%
“…However, some of the information that is available to people with MS is biased, inaccurate, and not evidence-based. One survey of 50 lay books on CAM found that MS was sometimes defined incorrectly, five or six therapies, on average, were recommended, no books had the same recommendations, and few books discouraged the use of any CAM therapies [4]. Vendors of CAM products may exaggerate claims, CAM practitioners and product vendors may have limited MS-specific information and experience, and, by definition, most conventional health care providers have little or no knowledge of, or experience with, CAM therapies.…”
Section: Opinion Statementmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the widespread use, studies on risks associated with the use of CAM still remain sparse, and a need for more research that enables patients to make informed treatment decisions has been emphasized by several authors [14][15][16][17][18][19][20][21][22][23][24]. The existing literature shows that benefits and low risk are associated with some specific CAM treatments used by MS and cancer patients when implemented properly [e.g., 14-16, 19, 25-27], while other treatments are considered unsafe or ineffective [e.g., [14][15][16]18]. In general, increased CAM use has been interpreted as a result of both a positive attitude toward CAM and a somewhat negative attitude toward conventional health care.…”
Section: Cam and Riskmentioning
confidence: 99%